1997
DOI: 10.1021/jp9639049
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Femtosecond Photoionization of NaI

Abstract: Two-color two-photon femtosecond ionization experiments have been performed on NaI. The wave packet evolution of the A excited state has been followed by detecting photoions and photoelectrons. The results indicate that the Na+ ions are formed when the wave packet is located at the outer turning point of the excited state. Surprisingly, the NaI+ ions are also observed to be in phase with the Na+ signal. Photoelectron spectra show that high kinetic energy electrons are produced when ionizing around the outer tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
95
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 22 publications
12
95
0
Order By: Relevance
“…1 shows exemplary delay scans extracted from our data at well-defined photoelectron energies of E k =1.8 ± .1 eV and E k =1.4 ± .1 eV, corresponding to the outer turn on the potential surface or to intra-molecular distances around the intersection, respectively. Similar response signals, characterizing the oscillating behavior were observed in [1,2,5]. However, our measurements can provide more detailed insights, as all electronic states of excited NaI, reachable with the ionizing probe pulses, were resolved at once ( fig.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…1 shows exemplary delay scans extracted from our data at well-defined photoelectron energies of E k =1.8 ± .1 eV and E k =1.4 ± .1 eV, corresponding to the outer turn on the potential surface or to intra-molecular distances around the intersection, respectively. Similar response signals, characterizing the oscillating behavior were observed in [1,2,5]. However, our measurements can provide more detailed insights, as all electronic states of excited NaI, reachable with the ionizing probe pulses, were resolved at once ( fig.…”
Section: Introductionsupporting
confidence: 68%
“…The experiments presented here can be seen as an extension of our former study of Br 2 dissociation [4]. A TRPES study with femtosecond pulses on NaI molecules has previously been done in 1997 by Jouvet et al [5], but in their experiment they could only distinguish between slow and fast electrons, hence not using the advantage of resolving all electronic states simultaneously. In this contribution, we present the results from our recent experiments on the electronic structure dynamics in photo-excited NaI molecules in a photon wavelength range covering 320 nm to 370 nm.…”
Section: Introductionmentioning
confidence: 91%
“…[1][2][3] In the presence of solvent molecules, the situation changes radically due to the strong coupling of the system ground and excited states with the interacting solvent field. 4 Visible or UV photoexcitation of many anionic solutes in solution and in clusters frequently leads to the appearance of optical charge-transfer absorption bands, located at lower ena͒ ergies than the vacuum detachment threshold; they are normally referred to as charge-transfer-to-solvent ͑CTTS͒ transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 depicts the spatial distribution of the CTTS electron excited from an I − ion and from a K + I − contact ion pair dissolved in ammonia, for a typical snapshot of a simulation run at a fluid density 1 * = 0.827 and T = 420 K. 22 Supercritical ammonia in the reduced density range 1 * = 0.07-0.83 was chosen as the solvent medium because by varying its density it was possible to have either free iodide ions or K + I − CIPs with sufficiently high concentrations to observe their optical absorption. 16 The optical excitation of iodide anions in supercritical NH 3 revealed that not only the free solvated anion but also the CIP species act as efficient CTTS donors. 16 However, the two CTTS states will exhibit marked differences between them due to the proximity of the potassium counterion to the donor in the CIP; K + ions dominate the solvent structure around the photoexcitable species producing substantial alterations with respect to the solvation structure in free iodide ion.…”
Section: Introductionmentioning
confidence: 99%
“…The pump-probe spectroscopy of NaI has been studied extensively [3,4,[15][16][17][18][19][20][21]. Figure 1 depicts the pump-probe scheme and the relevant potential curves for femtosecond photoelectron spectroscopy of the excited-state wave packet dynamics.…”
mentioning
confidence: 99%